Characterisation of the volatile compounds profile of Chinese pan-fried green tea in comparison with baked green tea, steamed green tea, and sun-dried green tea using approaches of molecular sensory science - Yali Shi; Yin Zhu; Wanjun Ma; Zhi Lin; Haipeng Lv (Current Research in Food Science, 2022)
Pan-fried green tea (PGT) is an easily acceptable tea drink for general consumers. In this study, volatile profiles and characteristic aroma of 22 representative Chinese PGT samples were extracted using stir bar sorptive extraction (SBSE) and analysed by gas chromatography-mass spectrometry (GC-MS), gas chromatography-olfactometry (GC-O) analysis, and odour activity value (OAV) calculations. In total, 88 volatile compounds were identified. Alcohols (45%), esters (19%), and ketones (16%) were the dominant volatiles, and geraniol (484.8 μg/kg) was the most abundant volatile component in PGT, followed by trans-β-ionone and linalool. In addition, the differences of aroma characteristics among PGT and other three types of green tea, namely baked green tea, steamed green tea, and sun-dried green tea, were also observed using partial least squares discriminant analysis (PLS-DA) and heatmap analysis, and it was found that β-myrcene, methyl salicylate, (E)-nerolidol, geraniol, methyl jasmonate were generally present at higher content in PGT. This is the first comprehensive report describing the volatile profiles of Chinese PGT, and the findings from this study can advance our understanding of PGT aroma quality, and provide important theoretical basis for processing and quality control of green tea products.